ACCURACY OF INTRAOPERATIVE RADIONUCLIDE SCINTIGRAPHY FOR DETECTION OF SENTINEL LYMPH NODE USING 99MTC LABELED NANOCOLLOIDS IN EARLY BREAST CARCINOMA: Intraoperative Radionuclide Scintigraphy - Dar, Zaigham Salim; Aziz, Omer bin Abdul; Sajid, Tanveer; Ali, Mujahid Khalid (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the accuracy of intraoperative radionuclide scintigraphy for detection of sentinel lymph node (SLN), using 99mTc-Nanocolloids, in patients with early breast carcinoma. Study Design: Cross sectional analytical study. Place and Duration of Study: Nuclear Medical Centre, Armed Forces Institute of Pathology, Rawalpindi and department of Surgery, Pak Emirates Military Hospital, Rawalpindi, from Jul 2012 to Jun 2013. Patients and Methods: After fulfilling the inclusion and exclusion criteria and taking written informed consent, 67 patients of carcinoma breast were enrolled in the study. Each patient was injected with 37 MBq of 99mTc- Nanocolloids, via sub areolar, peri-tumoural route, pre-operatively. SLNs were identified using handheld gamma probe followed by excision biopsy. Patients, then, underwent modified radical mastectomy with dissection of axillary lymph nodes (ALN) and the samples were sent for histopathology. Results: Out of 67 patients, 28 to 77 years of age (mean ± SD of 49.61 ± 11.572 years), 17.9% (12) patients had T1tumour while 82.1% (55) had T2 tumour (mean ± SD of 3.48 cm ± 1.050 cm). Histopathology revealed no metastasis in SLNs as well as ALN of 55.2% (37) patients while 40.3% (27) patients were positive for both. However, in 4.5% (3) patients SLNs were negative for metastasis with positive ALN. Diagnostic accuracy was calculated to be 95.5%, sensitivity 90%, false negative rate 4.5% and negative predictive value 92.5%. Conclusion: Intraoperative radionuclide scintigraphy, using 99mTc-Nanocolloids and handheld gamma probe is a reasonably accurate technique for localization of SLNs in early breast carcinoma.